Pengaruh Locus of Control, Tingkat Pendidikan, Pengalaman Kerja, dan Pertimbangan Etis terhadap Perilaku Auditor dalam Situasi Konflik Audit - Renata Zoraifi (Jurnal Akuntansi dan Bisnis, 2005)
Cognitive variable (ethical reasoning) is not enough to predict and to explain ethical behavior of accountant, so personality variables (locus of control, years of education, and years of employment) need to be interacted with this cognitive variable in order to reveal this matter. This research developed from Tsui and Gul (1996) research, but this study adds two personality variables that are years of education and years of employment. Previous research has found that interaction between locus of control and ethical reasoning has significant effect to auditor’s behavior in audit conflict situation. The purpose of this research is examining empirically whether the interaction between cognitive variable (ethical reasoning) and personality variables (locus of control, years of education, and years of employment) effect to auditor’s behavior in audit conflict situation. This research use survey method. Research population was small audit firm in Central Java and Yogyakarta. Sample of this research were auditors, which work in audit firm in Solo, Semarang, and Yogyakarta. Multiple regressions were used to test all hypotheses. Result from statistic test show that the interaction between cognitive variable (ethical reasoning) and personality variables (locus of control, years of education, and years of employment) has significant effect to auditor’s behavior in audit conflict situation.